4-H Horse and Pony Lease - E. L. Johnson; Wendy DeVito (EDIS)
This document contains the forms that might be needed for one 4-H'er to lease a horse: a page of instructions, a page of advice, the 3-page lease form, and 2 copies of the addendum (if up to two others are sharing Horse). This lease form was designed to cover the basic agreement between a 4-H member and a horse owner. If either party prefers to delete or edit any of the wording, or add more wording, it may be done as long as both parties agree and it does not alter any lease rules required by 4-H. Members of the general public leasing the same Horse as a 4-H youth are not required to use this particular form. However, anyone involved in a horse lease is encouraged to have similar agreements spelled out in writing. Original publication date March 2011.